(untitled) (Economics and region, 2023)
The article examines the main macroeconomic indicators of the national economy during a full-scale war. It is determined that over the past 10 years, Ukraine has been experiencing an increase in consumer spending and a reduction in gross domestic product, which is associated with significant migration abroad, in particular in the first months of the war. The article analyses the dynamics of changes in nominal and real GDP, inflationary processes, labour market and wages. It is revealed that, unfortunately, Ukraine experienced a significant deterioration in the economic situation in 2022, in particular: a fall in nominal GDP, a reduction in real wages, an increase in consumer prices, respectively, inflation, a decrease in retail trade, industrial, agricultural and construction products, exports of goods and an increase in imports. It is found that a positive factor in improving the situation was the actions of the NBU, which at the beginning of the war were aimed primarily at maintaining the stability of the banking system, uninterrupted payments and the adaptation of the economy, business and population to wartime conditions. In particular, in June 2022, the NBU raised the key policy rate to 25%, which made it possible to increase the attractiveness of hryvnia assets and reduce pressure on the foreign exchange market and international reserves. The main steps at the state level to develop specific and comprehensive measures for the development of key sectors of the Ukrainian economy are presented. It is established that increasing the economic activity of the population and providing employment opportunities for as many people as possible is a very important task for the country’s recovery. To increase employment, an integrated approach is needed to ensure inclusive development and to engage as many people as possible, regardless of gender, age, and people with disabilities, as their number is constantly growing.